Intravitreal drug injection for glaucoma: mechanisms, clinical efficacy, and future horizons - Lin, Bin; Shi, Peng; Li, Dong-Kan (Frontiers in Pharmacology, 2025)
Intravitreal drug injection has emerged as a transformative approach in glaucoma management, overcoming the limitations of traditional treatments such as poor compliance with topical medications and high complication rates of filtration surgery. This review synthesizes the mechanisms, clinical efficacy, and future directions of intravitreal drug injection in glaucoma management, with a focus on Anti-vascular endothelial growth factor (anti-VEGF) agents, sustained-release preparations, and intraoperative adjuvant injections. Anti-VEGF drugs, as the cornerstone for neovascular glaucoma (NVG), effectively regress iris neovascularization and reduce intraocular pressure (IOP), with aflibercept achieving an 86.7% regression rate and a 12.3 mmHg IOP reduction in clinical trials. Sustained-release preparations, leveraging porous structures or biodegradable carriers with differential pore sizes or degradation rates, enable long-term drug release (up to 6 months) and stable 1OP control, addressing the need for frequent injections. Intraoperative adjuvant injections, such as epinephrine during minimally invasive glaucoma surgery (MIGS), further enhance surgical success by reducing scarring and improving IOP control. Despite these advancements, challenges remain, including reliance on primary disease control for anti-VEGF efficacy, carrier displacement risks, and the lack of real-time drug concentration monitoring. Emerging technologies, such as intelligent responsive delivery systems, nanorobotics, and Clustered Regularly Interspaced Short Palindromic Repeats and CRISPR-associated protein 9 (CRISPR-Cas9) gene editing, offer promising solutions to achieve precise, individualized therapy. This review highlights the shift from passive IOP reduction to active neurovascular regulation, emphasizing the potential of intravitreal injection to redefine glaucoma treatment paradigms.